Evaluation of the efficiency of Russian universities: Do we need to change the paradigm? - E. V. Romanov (Образование и наука)
Introduction. The principles of managerialism have been actively applied in the field of higher education and science in Russia in the last decade. However, to a certain extent, such principles contradict the strategic goals for the breakthrough socio-economic, scientific and technological development of the country. Innovative development of the scientific and educational sphere is one of the conditions for this breakthrough. In this regard, the research works on the evaluation system of universities are becoming very relevant today. Thus, the evaluation system of universities allows the managers to perform a strategic function rather than a “fiscal” one - the formation of the strategic orientations of innovative development in the institutions of higher education within the framework of the implementation of the national development goals of Russia.The research aims to prove the statement that the existing system of evaluation of the efficiency of universities does not allow for a full objective assessment of their innovative potential and forms strategic guidelines, which do not correlate with the implementation of the goals for the breakthrough scientific and technological development of Russia. Moreover, the research is aimed to formulate the proposals for an approach to the evaluation of the activities of universities, according to which the basic performance indicators and their corresponding performance indicators are determined.Methodology and research methods. The research work was carried out based on a systematic approach. General scientific methods were used: an analytical review of scientific literature and the content of regulatory documents, comparison and generalisation (results of the evaluation of the efficiency of 215 universities under the Ministry of Education and Science according to the monitoring of universities in 2019, indicators of 34 federal and national research universities (monitoring 2016-2018)), induction (based on the analysis of the dynamics of the measurement of the average Unified State Exam (USE) score of applicants for technical universities, there is no correlation between this indicator and the employment of graduates), synthesis (formulation of the proposals for an approach to evaluate the activities of universities).Results and scientific novelty. The analysis of the existing approach to the evaluation of the efficiency of the activities of universities carried out within the framework of monitoring shows that the indicators are mainly input characteristics; thus, it does not give an idea of the independent achievements of the university, its contribution to the development of the country and the region. The author analysed the indicators of the Order by the Ministry of Education and Science № 475 (28.06.2020), under which the effectiveness of universities and their managers will be evaluated. It was found that the majority of “peripheral” technical universities have an “innate” sign of “inefficiency” - the average USE score of incoming applicants is less than 60, which was recorded during almost all monitoring measurements in 2013-2019. This leads to a zero rating on one of the indicators of the efficiency of educational activities and creates a false idea of the potential of organisations since the employment rates of graduates in the vast majority of universities in this category are above the threshold values. An analysis of the indicators of federal and national research universities (monitoring in 2016-2019) allows us to conclude that universities with a fairly low share of full-time teachers (up to 50 %) in the total number of teaching staff and the estimated number of research and teaching staff rates are significantly higher than their full-time number. Therefore, such universities can achieve fairly high rates of publication activity. A similar phenomenon is observed in higher education institutions, where the estimated number of vacancies is less than the full-time number of research and teaching staff (“vacancy manipulation effect”). Meanwhile, the income from the use of the results of intellectual activity, as the reflection of the university ability to develop commercially attractive products for the vast majority of universities, tends to zero. Based on the analysis of the income structure of federal and part of national research universities, the author proves that it is not correct to compare universities in terms of the volume and rate of income from income-generating activities.It is required to change the methodology for the evaluation of universities, i.e. to highlight performance indicators and their corresponding performance indicators (as the ratio of results achieved and costs). A correct assessment assumes the comparability of universities in terms of expected performance and the implemented “target function”: federal, national research, anchor universities, “ordinary” universities. Three groups of performance indicators are proposed to assess: a) the contribution of the university to the training of competent specialists with a developed system of values; b) the ability of the university to generate and disseminate new knowledge; c) the prospects for the reproduction of human resources at the university. Since the problem of personnel reproduction is of national importance, it is necessary to radically revise the principles of university funding: the state should finance the number of staff units justified by the university to ensure quality implementation of the main activity (during 4 years, at least).Practical significance. The research findings can be employed to adjust the development strategy of the scientific and educational sphere.